(NtWORI TA BUDE[ ]ASLIWIJ (B=s Creeaza si vei fi fericit - (NpOPESKU(B, )Qæ. (Nw(B.s)E ((N~ERN)QÆWCÆ (B:s)E (NrUTA(B,s, 2004)
(NkNIGA SKLADA)QÃTXSQ Z (B"(NsLOWO PRO AWTORA(B" ((Nw(B. (NkARLA]UK(B), "(NsPISOK WIBRANIH PUBLÆKACÆJ(B" (251), "(NnAUKOWÆ DOPOWÆDÆ TA POWÆDOMLENNQ(B" (37), "(NkRITI^NÆ OCÆNKI PRACX(B, (NPOZDOROWLENNQ Z DNEM NARODVENNQ(B" Æ "(NsENTIMENTALXNIJ ALXBOM(B" (36).s)E
(NrUM(B. (NMOW(B.s
Keywords: (Nl)QÆTERATUROZNAWSTWOs)E -- (NrUMUNSXKA L)QÆTERATURAs)E -- (Nl)QÆTERATURNÆ DÆQ^Æ(B.s)E